Myocardial late gadolinium enhancement cardiovascular magnetic resonance in patients with cirrhosis - Loßnitzer, Dirk; Steen, Henning; Zahn, Alexandra; Lehrke, Stephanie; Weiss, Celine; Weiss, Karl Heinz; Giannitsis, Evangelos; Stremmel, Wolfgang; Sauer, Peter; Katus, Hugo; Gotthardt, Daniel (Journal of cardiovascular magnetic resonance, 2010)
Portal hypertension and cardiac alterations previously described as "cirrhotic cardiomyopathy" are known complications of end stage liver disease (ELD). Cardiac failure contributes to morbidity and mortality, particularly after liver transplantation and transjugular intrahepatic portosystemic shunt (TIPS). We sought to identify myocardial tissue characterization and evaluate cardiovascular magnetic resonance (CMR) for diagnosis of cardiac impairment.
Gesehen am 18.04.2023